2010
DOI: 10.1186/1471-2431-10-78
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design and methods for a randomised and controlled trial to evaluate "Animal Fun" - a program designed to enhance physical and mental health in young children

Abstract: BackgroundChildren with poor motor ability have been found to engage less in physical activities than other children, and a lack of physical activity has been linked to problems such as obesity, lowered bone mineral density and cardiovascular risk factors. Furthermore, if children are confident with their fine and gross motor skills, they are more likely to engage in physical activities such as sports, crafts, dancing and other physical activity programs outside of the school curriculum which are important act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 58 publications
0
23
0
1
Order By: Relevance
“…Children for this study were drawn from a typically developing sample of 532 children ranging from 4 years and 3 months to 6 years and 11 months of age ( M = 5 years and 5 months, SD = 4.91). These children were involved in an intervention study (Piek et al, ) involving 12 low socio‐economic status pre‐primary schools in metropolitan and surrounding regional areas. Although we had access to longitudinal data, we chose to conduct cross‐sectional analyses on the pre‐test scores because of possible contamination from the intervention at subsequent assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Children for this study were drawn from a typically developing sample of 532 children ranging from 4 years and 3 months to 6 years and 11 months of age ( M = 5 years and 5 months, SD = 4.91). These children were involved in an intervention study (Piek et al, ) involving 12 low socio‐economic status pre‐primary schools in metropolitan and surrounding regional areas. Although we had access to longitudinal data, we chose to conduct cross‐sectional analyses on the pre‐test scores because of possible contamination from the intervention at subsequent assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also identified similar relationships where peer problems mediate the relationship between motor skills and internalizing problems in community samples of children (Wagner et al ., ; Wilson et al ., ). Improved perceived self‐competence and peer relationships have also been identified as potential targets in psychomotor interventions that aim to improve motor skills and psychosocial outcomes in children (Piek et al ., ). Consequently, these factors have been included in the current study to examine the extent to which they mediate the relationship between motor skills and internalizing problems.…”
Section: Introductionmentioning
confidence: 97%
“…Data were collected longitudinally, with pre‐test, post‐test (6 months later), and follow‐up (18 months later) data provided by participants as outlined by Piek et al . () as part of the Animal Fun study (Piek et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…No significant differences in age or verbal IQ ( M = 94.46, SD = 12.23) were found between boys and girls (i.e., independent‐sample t coefficient p > .05). Participants were recruited and measured as part of their involvement in the Animal Fun program (see Piek et al ., ). Linacre () demonstrated that a sample size of this magnitude would be expected to provide stable person measure and item calibration estimates within half a logit (with a calculable 99% CI) of accuracy.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation